Democratizing democracy : beyond the liberal democratic canon - Santos, Boaventura de Sousa (Verso, 2005)
The major conflicts between the north and the south can be expected to result from the confrontation of alternative conceptions of democracy, mainly between liberal or representative democracy and participatory democracy. The liberal, representative model of democracy, while prevailing on a global scale, guarantees no more than a low-intensity democracy. In recent times, however, participatory democracy has exhibited a new dynamic, engaging mainly subaltern communities and social groups that fight against social exclusion and the suppression of citizenship. In this collection of reports from the global South - India, South Africa, Mozambique, Colombia and Brazil - De Sousa Santos and his colleagues show how, in some cases, a deepening of democracy results from the development of dual forms of participatory and representative systems, and points to the emergence of transnational networks of participatory democratic initiatives. Such networks pave the way to the reinvention of social emancipation.